Znaczenie grupowych ubezpieczeń życiowych dla materialnego bytu rodziny - Nowak, Stanisław (Wydział Prawa i Administracji UAM, 1985)
The demand on material means indispensable to compensate effects of fortuitous events can be directed to various sources of compensation. A particular possibility of such compensation is created by property and personal economic insurances. Personal group insurances, including group family life insurances deserve the special attention in that group of insurances. They serve to cover material needs effected by illness, loss of a capacity to earn and loss of a principal earner. In that way they can substantially contribute to social security payments. They belong to the most popular and reckoned economic insurances. Their dynamic development since 1954 has reached the stage of almost total commonness among employees of the social sector of economy, eg. approximately 11.6 mln of persons were covered by that insurance for total of 12 mln of the social sector workers in 1980. The attempt at estimating the effectiveness of group life insurances cannot be an easy task as both in the insurance practice and theory there are no unmistakable indices defining that effectiveness in relation to social and economic spheres. If we adopt that a function of the discussed life insurances is to institute the immediate aid to family of a deceased worker or in case of death of co-insured family members then the effects of that insurance aid can be observed by comparing costs incurred by family effected by an unfortunate fortituous event (death of a family member) and indispensable expenses for maintaining the present living standard with a lump sum of benefits gained within the schedule of social and economic insurances. Under those conditions, a level of effectiveness of life insuarance will be related to the sum insured of both the principal insured and others insured. The insurance office has to follow socio-economic changes, eg. inflationary processes observed recently and adjust sums insured to the raising costs. In that way taking out insurances with top sums insured can cover the above mentioned expenses. The previous insurance practice indicates at indispensability of conducting research by insurers on the effect of those processes on the effectiveness of insurance protection and particularly at ascertaining interrelations and indices to make the level of insurance protection follow the changing socio-economic conditions of family existence.
The effect of group life insurances on a material position of family